College Algebra (6th Edition)

Published by Pearson
ISBN 10: 0-32178-228-3
ISBN 13: 978-0-32178-228-1

Chapter 4 - Exponential and Logarithmic Functions - Exercise Set 4.3 - Page 477: 66


$=\log_4(\sqrt[3] {\frac{x}{y}}(x+1)^{2})$

Work Step by Step

$= \frac{1}{3}(\log_4x-\log_4y)+2\log_4(x+1)$ $= \frac{1}{3}(\log_4\frac{x}{y})+\log_4(x+1)^{2}$ $= \log_4(\frac{x}{y})^{\frac{1}{3}}+\log_4(x+1)^{2}$ $= \log_4(\sqrt[3] {\frac{x}{y}})+\log_4(x+1)^{2}$ $=\log_4(\sqrt[3] {\frac{x}{y}}(x+1)^{2})$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.